Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/pssa.201532250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent additives on trap‐assisted recombination in P3HT:ICBA based polymer solar cells

Abstract: In this work, the effects of solvent additives on the trapping and recombination of carriers in polymer solar cells based on the blend of poly(3-hexylthiophene) (P3HT) and indene-C 60bisadduct (ICBA) are investigated by measuring the ideality factor and transient photocurrent. The addition of a few percent of 4-bromoanisole (BrAni) and 1-chloronaphthalene (CN) can give rise to the preferable morphology with well-ordered interpenetrating networks, which is beneficial for charge transport. Efficiency enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…[62,63] We obtained n = 1.32 for OSCs with neat P3HT:ICBA lightharvesting layers, which is in accordance with earlier literature reports. [64] Upon addition of F 4 TCNQ, n gradually increases up to 1.73 (w F TCNQ 4 = 0.4 wt%), hence indicating enhanced SRH recombination, which agrees well with the reduction of the V OC and the fill factor toward higher doping ratios. At even higher doping ratios, the developments of the key parameters are much more complex, as discussed in Section S6, Supporting Information.…”
Section: Solar Cells Fabricated From Electrically Doped P3ht:icba Nan...supporting
confidence: 70%
“…[62,63] We obtained n = 1.32 for OSCs with neat P3HT:ICBA lightharvesting layers, which is in accordance with earlier literature reports. [64] Upon addition of F 4 TCNQ, n gradually increases up to 1.73 (w F TCNQ 4 = 0.4 wt%), hence indicating enhanced SRH recombination, which agrees well with the reduction of the V OC and the fill factor toward higher doping ratios. At even higher doping ratios, the developments of the key parameters are much more complex, as discussed in Section S6, Supporting Information.…”
Section: Solar Cells Fabricated From Electrically Doped P3ht:icba Nan...supporting
confidence: 70%
“…It is similar to the drift velocity for the case of the band-like conduction mechanism. Whether the current transport mechanism is the band-like conduction mechanism or the hopping conduction mechanism, the experimental data of the current through an organic semiconductor diode can be described by the thermionic emission over the barrier [1], [2], [4], [6], expressed by the standard diode equation [3], [5], [7], [8]. All these results imply that the experimental organic diode currents have a similar mathematical expression.…”
Section: Theorymentioning
confidence: 82%
“…Numerous research efforts have been focused on not only improving the absorption of light but also enhancing the charge transport process via improved optical absorption, charge mobility and transport as well as morphology [9][10][11][12]. The incorporation of metallic, semiconducting and dielectric nanocomposite in the functional layers of BHJ OSCs plays important roles in the improvement of optical absorption, exciton generation, dissociation and transport of charge which in turn enhances the overall performance of the devices [13][14][15][16]. Metal nanoparticles (NPs) have found productive usage in all functional layers of thin film organic solar cell (TFOSCs) due to their excitation of localized surface plasmonic resonance (LSPR) and light scattering effect which leads to an improved photon-to-electron conversion efficiency.…”
Section: 1) Bulkhetrojunction Organic Solar Cellmentioning
confidence: 99%
“…Khatri et al [14] reported enhanced photovoltaic properties by introducing a combination of SWCNTs and functionalized multiwalled CNTs (MWCNTs) in poly(3octylthiophene) (P3HT)/n-silicon hybrid heterojunctions solar cells. Kuila et al [15] incorporated CNTs in the polymer matrix by grafting P3HT on the walls of CNTs via ester bonds and an efficiency of 0.29% was obtained for this cell. So far, the composites based on CNT did not produced the expected high performance organic solar cells because of the agglomeration tendency of the carbon nano tubes in the solution as well as in the film formation processes.…”
Section: Organic-organicmentioning
confidence: 99%